A comprehensive chemical abundance analysis of the extremely metal poor Leoncino Dwarf galaxy (AGC 198691). Issue 1 (10th November 2021) - Aver, Erik; Berg, Danielle A; Hirschauer, Alec S; Olive, Keith A; Pogge, Richard W; Rogers, Noah S J; Salzer, John J; Skillman, Evan D
ABSTRACT: We re-examine the extremely metal-poor dwarf galaxy AGC 198691 using a high quality spectrum obtained by the LBT's MODS instrument. Previous spectral observations obtained from KOSMOS on the Mayall 4-m and the Blue channel spectrograph on the MMT 6.5-m telescope did not allow for the determination of sulfur, argon, or helium abundances. We report an updated and full chemical abundance analysis for AGC 198691, including confirmation of the extremely low "direct" oxygen abundance with a value of 12 + log (O/H) = 7.06 ± 0.03. AGC 198691's low metallicity potentially makes it a high value target for helping determine the primordial helium abundance ( Y p ). Though complicated by a Na i night sky line partially overlaying the He i λ5876 emission line, the LBT/MODS spectrum proved adequate for determining AGC 198691's helium abundance. We employ the recently expanded and improved model of Aver et al., incorporating higher Balmer and Paschen lines, augmented by the observation of the infrared helium emission line He i λ10830 obtained by Hsyu et al. Applying our full model produced a reliable helium abundance determination, consistent with the expectation for its metallicity. Although this is the lowest metallicity object with a detailed helium abundance, unfortunately, due to its faintness [EW(Hβ) < 100 Å] and the compromised He i λ5876, the resultant uncertainty on the helium abundance is too large to allow a significant improvement on the measurement of Y p .